Costs and cost-effectiveness of the Safer Births Bundle of Care intervention in Tanzania health facilities - Boniphace Marwa; Corinna Vossius; Jan Terje Kvaløy; Benjamin Kamala; Pascal Mdoe; Hege Langli Ersdal; Frida N Ngalesoni; Albino Kalolo; Domenica Morona (PLoS ONE, 2026)
To reach the Sustainable Development Goals 3.1 to 3.4 for maternal, newborn, and child health, effective and cost-effective interventions are required. The Safer Births Bundle of Care (SBBC) intervention aims to improve the quality of intra- and postpartum care. The SBBC Phase I implementation was conducted in 30 health facilities in Tanzania between 2021 and 2023. Outcome data show a significant decrease in perinatal and maternal mortality. This study presents the costs of the SBBC Phase I, and a cost-effectiveness analysis, where the cost per life saved, per life year gained, and per disability-adjusted life year (DALY) averted, and the benefit–cost ratio (BCR) were estimated. Methods Outcome data were based on the estimated number of newborn and maternal lives saved during the project. Cost data were collected retrospectively at the accounting centre at Haydom Lutheran Hospital. Results The total cost for implementing SBBC Phase I was 4,491,204 USD. The cost per life saved was 4,669 USD, per life year gained 80 USD, and per DALY averted 144 USD, and the BCR was 36. Conclusion The analysis of SBBC Phase I showed that it was highly cost-effective by World Health Organization classifications. An economic evaluation of SBBC Phase II will provide information about its sustainability and feasibility for further scaling up.